1990
DOI: 10.1210/endo-126-5-2661
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Is a Mitogen for Isolated Epiphyseal Growth Plate Chondrocytes from the Fetal Lamb*

Abstract: Insulin acts directly as a mitogen on isolated embryonic tissues but has been shown to be inactive at physiological concentrations on several fetal cell types. Since insulin availability is obligatory for optimal fetal growth, we have investigated its mitogenic actions on chondrocytes isolated from the epiphyseal growth plates of fetal lambs. Chondrocytes were isolated from the proximal tibial growth plate of lamb fetuses between 40 and 130 days gestation using collagenase and were cultured in monolayer before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The increase could not be accounted for by an increase in the synthesis of total secretory proteins, because this remained relatively unchanged within culture medium after IGF treatment. Both IGFs were equally potent in stimulating IGFBP levels despite the finding that IGF-I was more effective as a mitogen than IGF-II in these cultures (Hill and De Sousa, 1990). IGFs can stimulate the production of IGFBPs by increasing IGFBP mRNA abundance (Bale and Conover, 1992;Camacho-Hubner et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…The increase could not be accounted for by an increase in the synthesis of total secretory proteins, because this remained relatively unchanged within culture medium after IGF treatment. Both IGFs were equally potent in stimulating IGFBP levels despite the finding that IGF-I was more effective as a mitogen than IGF-II in these cultures (Hill and De Sousa, 1990). IGFs can stimulate the production of IGFBPs by increasing IGFBP mRNA abundance (Bale and Conover, 1992;Camacho-Hubner et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Insulin availability is also intimately linked to the progression of normal and aberrant fetal growth. Hill and De Sousa (26) suggested that physiological concentrations of insulin might exert direct growth-promoting actions on the epiphyseal growth plates of the fetal lamb.…”
Section: Discussionmentioning
confidence: 99%
“…Hill and De Sousa (26) showed that fetal tissues are more sensitive to the trophic effects of insulin and that, at physiological concentrations, insulin has a mitogenic action on isolated fetal lamb epiphyseal chondrocytes. Ballock and Reddi (3) also observed that insulin maintained chondrocyte viability in the absence of cell hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Cell layers were washed and solubilized by 0·1 M sodium hydroxide. The total DNA content of cells within individual wells was measured by fluorimetry, using Hoechst fluorochrome 33258, as described previously (Hill & DeSousa 1990 …”
Section: Uptake Of [ 125 I] and Incorporation Of [ 3 H]thymidinementioning
confidence: 99%